2017
DOI: 10.1016/j.jenvrad.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in 137Cs concentrations in the bark, sapwood, heartwood, and whole wood of four tree species in Japanese forests from 2011 to 2016

Abstract: To understand the changes in radiocesium (Cs) concentrations in stem woods after the Fukushima Dai-ichi Nuclear Power Plant (FDNPP) accident, we investigated Cs concentrations in the bark, sapwood, heartwood, and whole wood of four major tree species at multiple sites with different levels of radiocesium deposition from the FDNPP accident since 2011 (since 2012 at some sites): Japanese cedar at four sites, hinoki cypress and Japanese konara oak at two sites, and Japanese red pine at one site. Our previous repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 20 publications
0
22
1
Order By: Relevance
“…S2). The simulated flux converged more quickly for pine trees (3 years) than for oak trees (5-7 years), and, as seen by the continuously rising 137 Cs activity concentration in oak wood 3,15 , the uptake flux was greater than the downward flux in oak trees. The observed 137 Cs activity concentration in cedar and oak wood showed different trends, and the modelling well reproduced the overall trends ( Fig.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…S2). The simulated flux converged more quickly for pine trees (3 years) than for oak trees (5-7 years), and, as seen by the continuously rising 137 Cs activity concentration in oak wood 3,15 , the uptake flux was greater than the downward flux in oak trees. The observed 137 Cs activity concentration in cedar and oak wood showed different trends, and the modelling well reproduced the overall trends ( Fig.…”
Section: Resultsmentioning
confidence: 92%
“…However, some potential limitations, which are sources of uncertainty, should be stated. Observations revealed that the 137 Cs activity concentration of sapwood and heartwood differed, particularly with that of cedar 15 . The prediction of 137 Cs activity concentration in wood may require explicitly dividing the sapwood and heartwood when the concentration in sapwood and heartwood differ considerably.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiation dose rates were also measured among different types of workers taking part in professional activities in the village of Kawauchi, where the annual doses of foresters (range: 0.7-1.9 mSv yr −1 ) were not significantly higher than those of farmers (0.7-1.5), builders (0.6-1.5), office workers (0.5-1.5) and unemployed individuals (0.5-1.7). In contrast, decontamination workers (0.5-7.1) were found to have significantly higher dose rates (Orita et al, 2017).…”
Section: Impact Of Decontamination On Dosimetrymentioning
confidence: 74%